①2*x²*(1/2-3xy+2y³)=x²-6x³y+2y²
②(x-3y)(x-5y)=x²-3xy-5xy+15y²
=x²-8xy+15y²
③(x+5y)(x-5y)=x²-25y²
④﹙x+2y﹚²=x²+4xy+4y²
⑤(2x-3)²=4x²-12x+9
⑥(-a)^6÷(-a)³=-a^6/a³
=-a³
⑦(-x²-y)²=(x²+y)²=x⁴+2x²y+y²
⑧1.、(2ab²)³-(9ab²)*(-ab²)²
=8a³b^6-9ab²*a²b⁴
=8a³b^6-9a³b^6
=-a³b^6
2、(-8x³y²+12x³y-4x²)÷|-(2x)²|
=4x²(-2xy²+3xy-4)/(2x)²
=4x²(-2xy²+3xy-4)/4x²
=-2xy²+3xy-4
3、(x-4y)(2x+3y)-(x-2y)(x-y)
=(2x²-5xy-12y²)-(x²-3xy+2y²)
= 2x²-5xy-12y²-x²+3xy-2y²
=x²-2xy-14y²
4、(2x+y-3z)(2x-y+3z)
=(2x)²-(y-3z)²
=4x²-y²+6yz-9z²
5、[(-2)^﹣³-8﹣¹·(-1)﹣²]*(π-3.14)º*(1/2)﹣²
=(-1/8-1/8*1)*1*4
=-1
⑨ [(2xy³)²+3x²*8xy]÷(-2x²y),其中x=2,y=-1
[(2xy³)²+3x²*8xy]÷(-2x²y)
=(4x²y^6+24x³y)/(-2x²y)
=4x²y(y^5+6x)/(-2x²y)
=-2(y^5+6x)
∵x=2,y=-1
∴原式=-2*[(-1)^5+6*2]
=-22
终于打完了(─.─|||,10分钟实在有些困难,我打字很慢的~